Algorithm approach for revision surgery following late-onset bleb complications after trabeculectomy: long-term follow-up - Perez,Claudio I. (2017)
ABSTRACT Purpose: The aim of this study was to introduce a reproducible algorithm for the surgical management of late-onset (>2 months) bleb complications after trabeculectomy with mitomycin C. Methods: We performed a retrospective review of eyes treated using a reproducible algorithm approach by a single surgeon for the surgical management of late-onset bleb complications from July 2006 to April 2014. Exclusion criteria were bleb revision with less than 3 months of follow-up or bleb revision combined with other glaucoma procedures at the time of surgery. Success was evaluated using the Kaplan-Meier survival method and defined as achieving all of the following criteria: primary surgery indication resolved, no additional surgery required for decreasing the intraocular pressure (IOP), and IOP of ≥6 mmHg and ≤18 mmHg. Results: Twenty-three eyes from 20 patients were evaluated. Indications for bleb revision were hypotonic maculopathy (47.8%), bleb leak (30.4%), and dysesthetic bleb (21.7%). The overall primary outcome success rate calculated using the Kaplan-Meier survival method was 65.2% at 48 months. When the IOP target was changed to ≤15 mmHg, the bleb survival rate was 47.8% at 48 months. At the most recent postoperative visit, 95.7% of eyes had an IOP of ≤15 mmHg and 56.5% were being treated with an average of one medication per eye. One eye (4.3%) required a second bleb revision for persistent hypotony and two eyes required glaucoma surgery to reduce IOP during follow-up. Conclusions: An algorithm approach for the surgical management of late-onset bleb complications with a success rate similar to those reported in specialized literature is proposed. Randomized trials are needed to confirm the best surgical approach.